Science and practice of strength training - Zatsiorsky, V. M.; Kraemer, W. J.; Fry, A. C. (Human Kinetics, 2021)
Science and Practice of Strength Training is a favorite book among strength and conditioning professionals. Now in a third edition, it offers upgraded artwork, updates based on current science, and new information to enhance the practical application of the concepts presented. A new coauthor, Dr. Andrew Fry, joins the already-popular author team of Dr. Vladimir Zatsiorsky and Dr. William Kraemer to make this third edition even better than its predecessors. Together the authors have trained more than 1,000 elite athletes, including Olympic medal winners, world champions, and national record holders. Influenced by both Eastern European and North American perspectives, their experience and expertise are integrated into solid principles, practical insights, and directions based on scientific findings.